Anthropological Observations on Science in the North: The Role of the Scientist in Human Development in the Northwest Territories - Bielawski, E. (ARCTIC, 1984)
The social context of research provides the background for assessing present and potential roles scientists may play in the Northwest Territories. This context includes diverse cultural and interest groups and an ever-quickening pace of social change. Increasing scholarly and ethical demands are being placed on the scientific community for academic accountability, public participation, education, and cross-cultural exchange of knowledge. These demands affect us, our disciplines, and our ability to carry on research. The Northern Cultural Heritage Project, an applied anthropology and archaeology program, serves as a case study illustrating the integration of research with the northern social context. Additional potential roles for researchers are discussed, including increasing information return, education through exposure to field science work, research ethics and social context awareness for novice professionals, and policy participation. It is concluded that the contemporary social context of the north has practical and perhaps theoretical implications for the conduct of science.Key words: anthropology, heritage, education, method, theory, policy, human resources, social context Mots clés: anthropologie, héritage, éducation, méthode, politique, ressources humaines, contexte social